1988
DOI: 10.1017/s0025315400028824
|View full text |Cite
|
Sign up to set email alerts
|

Sex Change in the Female Dog-Whelk,Nucella Lapillus, Induced by Tributyltin from Antifouling Paints

Abstract: Nucella lapillus were reared in the laboratory over a period of more than two years from hatching to maturity in waters containing tributyltin that had leached from an antifouling paint at concentrations of 1-2, 3-5, 20 and 100 ng Sn/1 in the TBT fraction. Penis and vas deferens formation in the female ('imposex') occurred at all TBT levels, development of these organs advancing further with increasing TBT concentration, the major part being observed during the first year of life. Normal egg capsule production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
125
2
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(135 citation statements)
references
References 15 publications
5
125
2
3
Order By: Relevance
“…It has been investigated on a large scale in the last few years with regard to increasing TBT (tributyltin) pollution resulting from the use of antifouling paints (Bright & Ellis, 1990;Gibbs et al, 1988;Oehlmann et al, 1992;Short et al, 1989;. TBT is also used as a biocide in various formulations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been investigated on a large scale in the last few years with regard to increasing TBT (tributyltin) pollution resulting from the use of antifouling paints (Bright & Ellis, 1990;Gibbs et al, 1988;Oehlmann et al, 1992;Short et al, 1989;. TBT is also used as a biocide in various formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile Buccinum undatum exposed to TBT, just after hatching, showed a dosedependent proportion of the young developing male sexual characters (Mensink et al, 1996), but no follow up study has been reported to ascertain whether the functional sex ratio is altered. Gibbs et al (1988) recorded suppression of oogenesis and production of sperm in female N. lapillus raised from hatched juveniles under the influence of TBT. The reproductive function of masculinization was not determined, and was believed to be hypothetical due to the absence of sterile female in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship meant that monitoring of TBT pollution can be effectively carried out based on the degree of imposex development in neogastropods in the receiving environment. Indeed, imposex in the female can occur at TBT concentration as low as 1 ng l À1 (Gibbs et al, 1988). The degree of imposex can be gauged by two main indices, namely relative penis size index (RPSI) and vas deferens stage index (VDSI) (Gibbs et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologically, apart from having the negative effects on oogenesis (Gibbs et al 1988;Oehlmann et al 1996;Horiguchi et al 2002), TBT also induces spermatogenesis in the ovaries of imposex females (Horiguchi et al 2002(Horiguchi et al , 2006. However, despite a report of extensive oocyte degeneration in Hexaplex trunculus (Axiak et al 2003), information on the effect of TBT on oogenesis in imposex females at the ultrastructural level is limited.…”
Section: Introductionmentioning
confidence: 99%